Critical success factors in digital publishing technology using an ANP approach - Shieh, Lon-Fon; Yeh, Ching-Chiang; Lai, Ming-Cheng (Technological and Economic Development of Economy, 2016)
Digital publishing technology (DPT) has been recognized as one of the most important technologies for economic development. The purpose of the study is to develop an evaluation model based on analytic network process (ANP) approach to explore the critical success factors (CSFs) for the successful implementation of DPT. It can objectively identify related criteria of DPT, and then prioritize improvement criteria to the success of promoting DPT for government. To demonstrate the applicability of the proposed approach, the Taiwan’s DPT is conducted. The results of this study could serve as a new method and offer insights to policy makers to indentify and prioritize CSFs for DPT implementations systematically.First published online: 03 Nov 2015